ENHANCEMENT AND INHIBITION OF IRON PHOTOREDUCTION BY INDIVIDUAL LIGANDS IN OPEN OCEAN SEAWATER - Rijkenberg M.J.A.; Gerringa L.J.A.; Carolus V.E.; Velzeboer I.; de Baar H.J.W. (My University, 2006)
In laboratory experiments, we investigated the effect of five individual Fe-binding ligands: phaeophytin, ferrichrome, desferrioxamine B (DFOB), inositol hexaphosphate (phytic acid), and protoporphyrin IX (PPIX) on the Fe(II) photoproduction using seawater of the open Southern Ocean. Addition of 10-100 nM Fe(III) to open Southern Ocean seawater without the model ligands and containing; 1.1 nM dissolved Fe(III), 1.75 ? 0.28 equivalents of nM Fe of natural ligands with a conditional stability constant (log K?) of 21.75 ? 0.34 and a concentration DOC of 86.8 ? 1.13 ?M C leads to the formation of amorphous Fe(III) hydroxides. These amorphous Fe(III) hydroxides are the major source for the photoproduction of Fe(II). The addition of the model ligands changed the Fe(II) photoproduction considerably and in various ways. Phaeophytin showed higher Fe(II) photoproduction than ferrichrome and the control, i.e., amorphous Fe(III) hydroxides. Additions of phytic acid between 65 and 105 nM increased the concentration of photoproduced Fe(II) with 0.16 nM Fe(II) per nM phytic acid, presumably due to the co-aggregation of Fe(III) and phytic acid leading via an increasing colloidal surface to an increasing photoreducible Fe(III) fraction. DFOB and PPIX strongly decreased the photoproduced Fe(II) concentration. The low Fe(II) photoproduction with DFOB confirmed reported observations that Fe(III) complexed to DFOB is photo-stable. The PPIX hardly binds Fe(III) in the open Southern Ocean seawater but decreased the photoproduced Fe(II) concentration by complexing the Fe(II) with a binding rate constant of kFe(II)PPIX = 1.04 ? 10-4 ? 1.53 ? 10-5 s-1 nM-1 PPIX. Subsequently, PPIX is suggested to act as a photosensitizing producer of superoxide, thus increasing the dark reduction of Fe(III) to Fe(II). Our research shows that the photochemistry of Fe(III) and the resulting photoproduced Fe(II) concentration is strongly depending on the identity of the Fe-binding organic ligands and that a translation to natural conditions is not possible without further characterization of the natural occurring ligands. ? 2006 Elsevier Inc. All rights reserved.
Keywords: IRON; LIGAND; OPEN OCEAN; PHOTOCHEMISTRY; REDUCTION; SEAWATER